Study of decomposing carbonyl slag - 陈爱良 孙培梅 赵中伟 李洪桂 陈星宇 (Transactions of Nonferrous Metals Society of China, 2006)
A new technology was put forward to deal with the carbonyl slag at low acidity and low oxygen pressure in the kettle. With the orthogonal experiments for analyzing the sequence of four factors and some single factor experiments for the best conditions. The best conditions are used for extracting nickel, cobalt and copper and enriching precious metals： the cupric ion concentration is 5 g/L; and pH=6; the sulfur coefficient is 1.4; the oxygen pressure is 0.08 MPa; the time bubbling oxygen is 20 rain; the ratio of liquid to solid is 8：1; the leaching time is 2 h; the heating time is 2.5 h. The leaching rates of nickel and cobalt are more than 98% and that of copper is above 97%. Nickel and cobalt can be separated efficiently from copper and precious metals from the carbonyl slag. Moreover, its leaching liquor has less copper. Nickel and cobalt can be reclaimed only once. During the whole process, the leaching rates of Au and Ag are more than 99.9%, while other precious metals are still in the residue without any loss.